Energy requirement for cotton crop in village Siwas (Dist. Pali) of Thar desert - Mohnot, Ranjan; Singh, Harpal; Lakhera, K C; Singh, Kaushal; Srivastava, R; Goyal, D (Journal of Agricultural Engineering, 2000)
Assessment of energy requirement for cultivating cotton crop in village Siwas, district Pali (Zone-IV) was done. A total of 70 farmers of the village have sown the cotton crop but only 56 farmers could take the crop successfully. The crop of the remaining 14 farmers failed due to drought prevailed during 1999-2000, as these farmers did not have adequate irrigation facility. The total energy requirement for cultivating cotton crop in the village was 19400 MJ/ha whereas operation energy contribution was about 60% of the total energy input. Energy ratio and specific energy required for raising cotton crop was 7.0 and 12.50 MJ/kg, respectively. Simple and multiple regression analysis were used to obtain best fit relations between energy input and crop yield revealing significant variability. The value of multiple RÂ² was 0.44. The joint linear effect of all energy input components on yield was significant (P&lt0.01), but individually all components have not contributed significantly.